Anomalous Experiences, Trauma, and Symbolization Processes at the Frontiers between Psychoanalysis and Cognitive Neurosciences - Rabeyron, Thomas; Loose, Tianna (Frontiers in Psychology, 2015)
Anomalous or exceptional experiences are uncommon experiences which are usually interpreted as being paranormal by those who report them. These experiences have long remained difficult to explain, but current progress in cognitive neuroscience and psychoanalysis sheds light on the contexts in which they emerge, as well as on their underlying processes. Following a brief description of the different types of anomalous experiences, we underline how they can be better understood at the frontiers between psychoanalysis and cognitive neurosciences. In this regard, three main lines of research are discussed and illustrated, alongside clinical cases which come from a clinical service specializing in anomalous experiences. First, we study the links between anomalous experiences and hallucinatory processes, by showing that anomalous experiences frequently occur as a specific reaction to negative life events, in which case they mainly take the form of non-pathological hallucinations. Next, we propose to analyze these experiences from the perspective of their traumatic aspects and the altered states of consciousness they often imply. Finally, these experiences are considered to be the consequence of a hypersensitivity that can be linked to an increase in psychic permeability. In conclusion, these different processes lead us to consider anomalous experiences as primary forms of symbolization and transformation of the subjective experience, especially during or after traumatic situations.